J-PLUS: Tomographic analysis of galaxy angular density and redshift fluctuations in Data Release 3. Constraints on photo-$z$ errors, linear bias, and peculiar velocities - Carlos Hernández-Monteagudo; A. Balaguera-Antolínez; R. von Marttens; A. del Pino; A. Hernán-Caballero; L. R. Abramo; J. Chaves-Montero; C. López-Sanjuan; V. Marra; E. Tempel; G. Aricò; J. Cenarro; et al. (The Open Journal of Astrophysics)
The Javalambre Photometric Local Universe Survey (J-PLUS) is a spectro-photometricsurvey covering about 3,000~deg$^2$ in its third data release (DR3), and containing about 300,000 galaxies with high quality ({\it odds}$>0.8$) photometric redshifts (hereafter photo-$z$s). We use this galaxy sample to conduct a tomographic study of the counts and redshift angular fluctuations under Gaussian shells sampling the redshift range $z\in[0.05,0.25]$. We confront the angular power spectra of these observables measured under shells centered on 11 different redshifts with theoretical expectations derived from a linear Boltzmann code ({\tt ARFCAMB}). Overall we find that J-PLUS DR3 data are well reproduced by our linear, simplistic model. We obtain that counts (or density) angular fluctuations (hereafter ADF) are very sensitive to the linear galaxy bias $b_g(z)$, although weakly sensitive to radial peculiar velocities of the galaxy field, while suffering from systematics residuals for $z>0.15$. Angular redshift fluctuations (ARF), instead, show higher sensitivity to radial peculiar velocities and also higher sensitivity to the average uncertainty in photo-$z$s ($σ_{\rm Err}$), with no obvious impact from systematics. For $z<0.15$ both ADF and ARF agree on measuring a monotonically increasing linear bias varying from $b_g(z=0.05)\simeq 0.9± 0.06$ up to $b_g(z=0.15)\simeq 1.5± 0.05$, while, by first time, providing consistent measurements of $σ_{\rm Err}(z)\sim 0.014$ that are $\sim 40~%$ higher than estimates from the photo-$z$ code {\tt LePhare}, ($σ_{\rm Err}^{\rm LePhare}=0.010$). As expected, this photo-$z$ uncertainty level prevents the detection of radial peculiar velocities in the modest volume sampled by J-PLUS DR3, although prospects for larger galaxy surveys of similar (and higher) photo-$z$ precision are promising.